2000
DOI: 10.1021/jp993484y
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Dynamics of Coumarin 480 in Sol−Gel Matrix

Abstract: Solvation dynamics of Coumarin 480 (C-480) in a tetraethyl orthosilicate (TEOS) sol-gel matrix has been studied using time-resolved emission spectroscopy. In the macroscopically solid TEOS matrix the solvation dynamics of C-480 is described by a major (85%) component of 120 ( 20 ps and a minor (15%) component of 800 ( 100 ps. These components are substantially slower than the solvation dynamics in bulk water. The rotational relaxation time of C-480 in this matrix is found to be very short (<80 ps).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 39 publications
3
102
0
Order By: Relevance
“…10 One consistent conclusion of their studies is that there is not a one-to-one correspondence between steady-state spectra and the time-dependent Stokes shift function, S(t): ''...steady-state spectroscopy may not always be a good predictor for dynamical behavior.'' 14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites.…”
Section: Experimental Workmentioning
confidence: 99%
“…10 One consistent conclusion of their studies is that there is not a one-to-one correspondence between steady-state spectra and the time-dependent Stokes shift function, S(t): ''...steady-state spectroscopy may not always be a good predictor for dynamical behavior.'' 14 Bhattacharyya and co-workers have measured the timedependent fluorescence of the dye molecule, Coumarin 480, in solventless zeolites, 4 aqueous micelles 5 and reverse micelles, 6 in water pools in a sol-gel matrix, 7 and vesicles. 8 They found that the long-time solvation dynamics depend strongly on the environment with a long-time decay of ϳ0.8 ns in the sol-gel matrix, 7 0.6 -2.4 ns in micelles ͑using different surfactants͒, 5 8 -12 ns in reverse micelles, 6 11 ns in vesicles, 8 and ϳ15.4 ns in the solventless zeolites.…”
Section: Experimental Workmentioning
confidence: 99%
“…30,31 In particular, these coumarins have been widely used as excited-state electron acceptors to study electron transfer from electron-donating solvents such as aromatic amines. 7,[32][33][34][35][36][37] Another application of the 7-aminocoumarins, especially the 3-carboxylic acid derivatives, has been as photosensitizing dyes for wide band gap semiconductors such as TiO 2 and ZnO. 24,[38][39][40][41][42] Excited-state proton-transfer reactions have also been widely studied using 7-aminocoumarins.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of hydrolytic, oxidation, and reduction reaction may also be significantly influenced by the reverse micelles [7,8]. Among the various surfactants present, most of the experiments have been done on sodium 1,4-bis(2-ethylhexyl)sulfosuccinate (AOT) [9][10][11][12][13][14][15][16]. Although potentially important, reverse micelles of the surfactants other than AOT are rare in the literature.…”
Section: Introductionmentioning
confidence: 99%